Simplify the following expression:

.`START_INT`\sqrt{`RADICAL_TOTAL`}

First, try to factor a perfect square out of the radical.

`= `

`START_INT`\sqrt{`RADICAL_TOTAL`}

`= `

`START_INT`\sqrt{`pow( RADICAL_INT , 2 )` \cdot `RADICAL_PRIME`}

Separate the radical and simplify.

`= `

`START_INT`\sqrt{`pow( RADICAL_INT , 2 )`} \cdot \sqrt{`RADICAL_PRIME`}

`= `

`START_INT` \cdot `RADICAL_INT` \cdot \sqrt{`RADICAL_PRIME`}

`= `

`START_INT * RADICAL_INT`\sqrt{`RADICAL_PRIME`}

Simplify the following expression:

.`START_INT`\sqrt{`RADICAL_TOTAL`}

There are no perfect-square factors of `RADICAL_TOTAL`.

Thus, the expression is already in its most simplified form.

`= `

`START_INT`\sqrt{`RADICAL_TOTAL`}